The law for institutes of consecrated life and societies of apostolic life: an introduction to Canons 573-746 - Tibi, Daniel (Liturgical Press, 2025)
"This book provides an up-to-date, comprehensive presentation of the Law of Institutes of Consecrated Life and Societies of Apostolic Life according to the 1983 Code of Canon Law. It is intended as an introduction for superiors and members of institutes and societies, as well as for vicars and officials in ecclesiastical administration. It will also serve as a useful resource for novitiate formation, and an initial overview for students engaged in academic study"--